Analysis of EYD Writing Errors in Student Assignments in Indonesia Language Learning Official Letter Material Class VII MTs. Roudlotur Rosmani Bengkulu City - Sitti Fathiah Fajriani; Irwan Satria; Vebbi Andra (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2024)
This research aims to describe the forms of EYD Writing Errors in Student Assignments in Indonesian Language Learning Official Letters Material Class VII at MTs Roudlotur Rosmani Bengkulu City and the factors that cause EYD Writing Errors in Student Assignments in Indonesian Language Learning Official Letters Material Class VII at MTs Roudlotur Rosmani, Bengkulu City. This research uses a qualitative approach with descriptive methods. The data collection techniques in this research are observation, interviews, and documentation techniques. The data in this research were obtained from 15 official letters written by class VII students at MTs Roudlotur Rosmani. The results of this research show that there are three forms of EYD writing errors, namely errors in using letters, writing words, and using punctuation marks. The results of this research also found the factors that cause EYD writing errors in the task of writing official letters by class VII students at MTs Roudlotur Rosmani, namely students' low knowledge of writing rules, neglect of writing rules, students' habits of not revising the results of writing assignments, and class conditions that are not conducive.